Arbeitskultur in der Industrie in der Volksrepublik Polen (1950-1989) [Working culture in industry in the People’s Republic of Poland (1950-1989)] - Kamosiński, Sławomir (Studia Historiae Oeconomicae, 2009)
The socialist system did not find a practical answer to the question of how to combine the problem of work performance and the innovative orientation of employees with the principle of full employment and the rejection of the market as a natural verifying factor of all economic activities. Therefore, the creation of work culture was a task that the leadership of the People's Republic of Poland could not cope with. In this respect, appeals to symbols of industrialization, of which Nowa Huta took first place, did not help. To a lesser extent, ideology also served this purpose, which was supposed to have influenced even private life. The system of vocational and technical education systematically developed in the People's Republic of Poland could not take on this task either.